Green's cuisine : low fat food with a taste of Thailand - Green, Daniel (Bangkok, Thailand : Book Promotion & Service, 2003)
Daniel Green believes that healthy eating doesn't mean dull eating and in this book he has developed 80 fun and exciting low fat recipes for a healthy diet, many with a taste of Thailand. Concise and easy to use, each recipe has preparation and cooking times an is accompanied by a superb colour photograph.
Includes index
Keywords: Cookery, Thai; Low-fat diet -- Recipes